Chronological Changes in Postprandial Blood Glucose Level of Labeo rohita (Hamilton, 1822) Fed with Formulated Diet - Sahoo, S.; Rani, S.; Singh, D.K.; Pailan, G.H. (Indian Journal of Animal Nutrition, 2022)
In general, fish is considered as a natural diabetic animal. In order to understand how the feed is metabolized to glucose and the time duration for its complete uptake from blood, a study was conducted to estimate the pre and postprandial blood glucose level in Labeo rohita, at two-hour intervals of both fasting and fed state. The blood glucose levels of four replicates at every time point were estimated using glucose oxidase method. The pre-prandial/ fasting blood glucose level was found to be in the range of 10-18 mg/dl. Whereas, two hours post-prandially the blood glucose level had got increased and estimated to be varying between 46-88 mg/dl, which was maximum. Also, it was observed that the sugar levels got reduced back to normal/fasting state after about 10hrs. Time period shows significant inverse relationship with blood glucose level (p